2016
DOI: 10.7554/elife.08133
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ-dependent expression of PD-1 and PD-L1 controls CD8+ T cell anergy in transplant tolerance

Abstract: CD8+ T cell anergy is a critical mechanism of peripheral tolerance, poorly investigated in response to immunotherapy. Here, using a pancreatic islet allograft model and CD3 antibody therapy, we showed, by single cell gene profiling, that intragraft CD8+ lymphocytes coexpressing granzyme B and perforin were selectively depleted through the Fas/FasL pathway. This step led to long-standing anergy of the remaining CD8+ T cells marked by the absence of cytotoxic/inflammatory gene expression also confirmed by transc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
86
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 51 publications
10
86
3
1
Order By: Relevance
“…Reduced expression of the AP-1 complex was also noticed in tolerant T cells infiltrating islet allografts after anti-CD3 antibody [62]. Moreover, CD8+ T cells isolated from tolerated islet allografts failed to produce IFNγ in response to donor antigens [62].…”
Section: Ii) Tolerance Mechanisms Associated With Transient Mixed Chimentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced expression of the AP-1 complex was also noticed in tolerant T cells infiltrating islet allografts after anti-CD3 antibody [62]. Moreover, CD8+ T cells isolated from tolerated islet allografts failed to produce IFNγ in response to donor antigens [62].…”
Section: Ii) Tolerance Mechanisms Associated With Transient Mixed Chimentioning
confidence: 99%
“…Moreover, CD8+ T cells isolated from tolerated islet allografts failed to produce IFNγ in response to donor antigens [62]. Single cell PCR of individual graft-infiltrating CD8+ T cells revealed high expression of the inhibitory receptors LAG-3, TGF-β-induced PD-1, PDL-1, as well as increased expression of Eomes in tolerant compared to control CD8+ T cells [62], highly suggestive of T cell exhaustion [55].…”
Section: Ii) Tolerance Mechanisms Associated With Transient Mixed Chimentioning
confidence: 99%
See 1 more Smart Citation
“…As Ni and colleagues only showed an increase in systemic IFN-γ levels in the absence of CD4 + T cells, it would be important to delineate whether IFN-γ expression is also increased within the local environment. Similarly, in addition to IFN-γ, other cytokines, such as IL-27 and TGF-β, can upregulate expression of PD-L1 (25,26). Although Ni et al found no notable differences in serum IL-27 concentrations in recipients treated with anti-CD4 mAb compared with a finding using multiple GVHD models (two murine allogeneic HCT models and a human → mouse xenogeneic HCT model) and two tumor models, including one that was previously shown to be partially resistant to the GVL effect (23).…”
Section: Gvl Versus Gvhdmentioning
confidence: 99%
“…Повышенное значение VEGF, TGF и IL10 в опухолевом микроокружении так-же способствует развитию резистентности к анти-PD1 терапии, предотвращая активацию опухоль-специфи-ческих Т-лимфоцитов [44,45,46]. Более того, на ксе-нографтах мышей было продемонстрировано, что TGF модулирует экспрессию PD-1 и PD-L1 [47]. Ко-экспрес-сия других ингибиторных рецепторов в дополнение к PD-1, таких, как TIM3 (T-cell immunoglobulin mucin 3), LAG3 (lymphocyte activation gene 3), CTLA4 и BTLA (B and T lymphocyte attenuator), ассоциируется с раз-витием резистентности к анти-PD1 терапии, что было продемонстрировано при немелкоклеточном раке лег-кого [48].…”
Section: механизмы резистентности к ингибиторам чекпоинтовunclassified